2021
DOI: 10.1139/bcb-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the systemic effects of oral lactoferrin: transcriptome profiling

Abstract: The immunomodulatory nature of lactoferrin (LF) derives from its ability to bridge innate and adaptive immunity in obtaining physiological equilibrium. LF is an attractive molecule for treatment of diseases that compromise immune homeostasis. Oral delivery is a preferable method for LF administration; however, its bioavailability is affected by protein degradation and absorption. The aim of this study was to evaluate the systemic effects of oral and intravenous (IV) administered recombinant human LF (rhLF) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Our study showed improvements in COVID-19 symptoms including fever, dry cough, diarrhea, headache, loss of sense of taste and/or smell and tiredness after the seventh day of starting treatment with Lf in all groups, however these changes showed no statistically significant difference among studied groups. These findings can be explained by the established broad-spectrum antiviral, anti-inflammatory and immunomodulatory properties of Lf [ 11 , 22 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed improvements in COVID-19 symptoms including fever, dry cough, diarrhea, headache, loss of sense of taste and/or smell and tiredness after the seventh day of starting treatment with Lf in all groups, however these changes showed no statistically significant difference among studied groups. These findings can be explained by the established broad-spectrum antiviral, anti-inflammatory and immunomodulatory properties of Lf [ 11 , 22 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin (LF) is the first line of defense proteins present in mammals, can treat diseases that impair immune homeostasis through immunomodulation, and has the ability to bridge innate immunity and adaptive immunity [86]. In rats, the comparison of differentially expressed genes after 6 h of LF oral and intravenous injection showed that 72.8% of gene changes after oral recombinant human LF (rhLF) administration were the same as those after the intravenous treatment.…”
Section: Oral Dietary Control Of Oxidative Stressmentioning
confidence: 99%
“…These two pathways show similarities in the upregulation of specific genes related to oxidative stress and inflammation. Therefore, LF can be supplemented through oral administration [86].…”
Section: Oral Dietary Control Of Oxidative Stressmentioning
confidence: 99%
“…In this way LTF may augment the immunity of all mucous membranes (eyes, gastrointestinal, urinary and reproductive tracts and airways) protecting against penetration of pathogens and development of excessive inflammation [ 58 , 112 ]. LTF, applied orally to rats, altered expression of numerous genes, such as genes coding for IL-1β, TNF-α, TNF-β and cellular receptors CD40L, CD80, IL-5R on peripheral blood leukocytes, similarly to the effects of intravenously administered LTF [ 113 ].…”
Section: Lactoferrin As a Diet Supplementmentioning
confidence: 99%